2018
DOI: 10.1016/j.apsoil.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of Fe resonates to the belowground rhizosphere microbiome in Andean landrace potatoes

Abstract: Iron (Fe) is a crucial nutrient for plant growth (e.g. chlorophyll production), and though it is one of the most abundant elements in soil, very low bioavailability can limit plant growth. Studies indicate that many soil bacteria and fungi (e.g. mycorrhizal) play a role in Fe nutrient cycling and plant production, but the evidence for fungal support of plant growth is overwhelmingly correlative and in need of experimental corroboration. An Andean native potato landrace was grown in a greenhouse under Fe limita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 84 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…The foliar application of 5.0 g L −1 ZnO nanoparticles can increase the soil microbial counts and enzyme activities in rice cultivated under low soil Zn concentrations (Bala et al 2019). Xiao et al (2018) reported that Fe fertilization of potato leaves had a significant effect on the beta diversity of fungi; foliar addition of Fe was suggested to influence plant Fe levels, entering the root system to affect rhizosphere fungal communities. Moreover, the application of foliar fertilizers can reduce salt accumulation in the soil to a certain extent.…”
Section: Effects On Soil Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The foliar application of 5.0 g L −1 ZnO nanoparticles can increase the soil microbial counts and enzyme activities in rice cultivated under low soil Zn concentrations (Bala et al 2019). Xiao et al (2018) reported that Fe fertilization of potato leaves had a significant effect on the beta diversity of fungi; foliar addition of Fe was suggested to influence plant Fe levels, entering the root system to affect rhizosphere fungal communities. Moreover, the application of foliar fertilizers can reduce salt accumulation in the soil to a certain extent.…”
Section: Effects On Soil Qualitymentioning
confidence: 99%
“…For example, excess P becomes "fixed" in soil, where it forms chemical bonds with other elements, including calcium (Ca), magnesium (Mg), iron (Fe), and zinc (Zn), and becomes unavailable for plant uptake (Raliya et al 2018). Therefore, although nutrients may be abundant in soil, low bioavailability will restrict plant growth and reduce fertilizer utilization (Xiao et al 2018), with unused nutrients temporarily accumulating in the soil or being lost to air or water. Compared with root fertilization, foliar fertilization, as a supplementary fertilization strategy, can deliver nutrients directly to the target through aerial plant parts, thereby helping to reduce negative impacts on the soil (Bindraban et al 2015;Fernández and Eichert 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Less well understood is how foliar application of seaweed extract could influence plant–microbe signaling and the structure of the rhizospheric microbiome. Foliar application of nutrients, hormones, or pathogens 24 , 41 , 42 has been shown to result in systemic responses that modulate rhizospheric microbial community structure. In the present study, foliar ANE application did not result in statistically significant increases in mature mycorrhization, but did elicit expression of mycorrhizal accommodation-related genes in the distal M. truncatula roots.…”
Section: Discussionmentioning
confidence: 99%
“…Seaweed extracts are also regularly applied foliarly in the field, yet thus far there have been no studies reporting the influence of foliar applications of seaweed-based biostimulants on AMF colonization. Through elicitation of a systemic response, foliar applications could potentially be expected to modulate root exudation and affect the establishment of plant–microbe associations 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…by enhancing photosynthetic performance [27]. Potato plants are associated with complex microbiomes, particularly in below-ground compartments [28,29], however, the response of the potato microbiome to abiotic stress, particularly drought, and its role for stress mitigation is poorly investigated. Here, we compared ten different potato cultivars grown in the eld under combined drought and P limited conditions, and particularly assessed the link of plant growth, yield traits and belowground plant microbiome composition.…”
Section: Introductionmentioning
confidence: 99%